O erotismo na ausência do corpo? uma investigação sobre o uso de aplicativos de encontro por mulheres e seus ideais - Lopes, Cláudia Mazur (2019)
Dating apps like Tinder and Happn represent a change that has achieved great popularity: the eroticism in the age of the internet. We understand eroticism not as solely restricted to sex, but as anything arousing, not necessarily physical, that feeds our desire. Historically, eroticism has presented itself in several spaces. However, a new phenomenon has recently drawn attention: the digital world as a means to experience erotic emotions, inasmuch as most of the modes of social interaction have migrated to virtual networks. In recent years, the creation of apps for said most diverse amorous “encounters”, ranging from casual sex up to more “serious” relationships. Unlike traditional social networks, dating applications have been developed with mobility in mind, and constantly available at the tap of a finger. This feature allows for a faster approach for future meetings. What do we expect from app-mediated affective relationships? There is concern regarding the methods used; all users present themselves through carefully crafted profiles and connect with their pairs searching for an experience. Proper use of these new communicative platforms is important, and for such the profile must be admired. One needs to show interest in “presenting oneself” as something of value. Faced with the cult of over-performance, in practice what they do is to encourage users to meet dating goals. Thus, we can assume that the greatest strength of the dating app is in the conjunction of factors: affection and market, which together produce an intensity of consumption that represents the materialization of something highly complex. The basis of this research is a study of the relationships between the use of applications and eroticism in the construction of contemporary subjectivity. For such, a theoretical basis that includes psychoanalysis authors, specialists in new technologies and in matters of the heart was used to do so